Profits in the Perspective of Traditional Market Traders in Gresik, East Java Province, Indonesia - Rahmat Agus Santoso; Anita Handayani; Niswatul Azifah (Universitas Sebelas Maret, 2022)
Traditional merchants’ profits are not limited to revenue gained over and above costs and expenses, but also include perks such as satisfying life's demands while maintaining a sense of happiness and long-term business relationships. The purpose of this research is to describe the phenomenon of the meaning of profit for traders in the perspective of Gresik culture. This research method is with a qualitative paradigm using an ethnographic approach. Collecting data using participant observation and in-depth interviews conducted by snowball. Test the validity of the data using the member check. Data analysis using the Spradley model. The research results that have been found, the meaning of profit for traders in the perspective of Gresik culture is courtesy, trust, and empathy.Keywords: culture; profit; trader; traditional market